2012
DOI: 10.3904/kjim.2012.27.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Hemoglobin Concentrations and the Clinical Characteristics of Patients with Type 2 Diabetes

Abstract: Background/AimsMany studies have demonstrated an association between hemoglobin levels and cardiovascular disease in diabetic patients. The aim of this study was to determine whether there is an association between hemoglobin concentrations and various clinical parameters, including metabolic factors, plasma C-peptide response after a meal tolerance test, and microvascular complications, in Korean patients with type 2 diabetes.MethodsIn total, 337 male patients with type 2 diabetes were recruited. All subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
2
5
0
Order By: Relevance
“…Compared with patients with ≤ 10 years duration of DM, the odds ratio of developing anemia in individuals with ˃ 10 years was approximately three times. This finding is in agreement with the previous studies in Australia, 12 Korea, 76 India, 49,77 and Finote Selam. 32 The reason for this increased chance of anemia development with an increasing duration of DM may be due to the chronic effects of hyperglycemia.…”
Section: %supporting
confidence: 94%
“…Compared with patients with ≤ 10 years duration of DM, the odds ratio of developing anemia in individuals with ˃ 10 years was approximately three times. This finding is in agreement with the previous studies in Australia, 12 Korea, 76 India, 49,77 and Finote Selam. 32 The reason for this increased chance of anemia development with an increasing duration of DM may be due to the chronic effects of hyperglycemia.…”
Section: %supporting
confidence: 94%
“…In our previous study that was conducted in 337 male patients with type 2 DM, we found an independent association between Hb concentrations and ΔC-peptide concentrations, [ 35 ] implying that Hb might be related to C-peptide concentrations. In the present study, we observed that the presence of anemia was inversely associated with the fasting C-peptide, postprandial C-peptide, and ΔC-peptide concentrations in the multivariable analysis, and these relations were independent of gender.…”
Section: Discussionmentioning
confidence: 82%
“…Low hemoglobin concentrations are more common in diabetic patients than nondiabetics and hyperglycemia has been shown to decrease red cell survival by 13%. 56 There may be an increased risk of severe diabetic retinopathy in individuals with hemoglobin levels below 12 g/dL, 57 , 58 although this association diminished after adjusting for diabetes duration in another study. 56 Lastly, a cross-sectional study of over 3000 patients found elevated serum calcium to be a risk factor for vision-threatening diabetic retinopathy, 59 and in vivo histology of the retina revealed elevated serum calcium was associated with retinal photoreceptor apoptosis in diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 91%